Analysis of competition in the global market of information and communication technologies: how China became a leader - Goloventchik, Galina G.; Chengrong, Ge (Journal of the Belarusian State University. Economics, 2024)
A system of key indicators and models for analysing the dynamics of the country’s competitive positions in the global industry market is proposed. As an example, we consider the most important market in the age of the digital economy – market of goods and services related to information and communication technologies. The factors that have made China a world leader in this market are identiﬁed. The vulnerabilities of Chinese commodity exports in the ﬁeld of information and communication technologies and ways to eliminate them are indicated.
Keywords: information and communication technologies; ICT market; competition in the market of ICT goods; competition in the market of ICT services